25 Years of Ed Tech - Weller, Martin (Athabasca University Press, 2021)
In this lively and approachable volume based on his popular blog series, Martin Weller demonstrates a rich history of innovation and effective implementation of ed tech across higher education. From Bulletin Board Systems to blockchain, Weller follows the trajectory of education by focusing each chapter on a technology, theory, or concept that has influenced each year since 1994. Calling for both caution and enthusiasm, Weller advocates for a critical and research-based approach to new technologies, particularly in light of disinformation, the impact of social media on politics, and data surveillance trends. A concise and necessary retrospective, this book will be valuable to educators, ed tech practitioners, and higher education administrators, as well as students.